Réflexions sur la déchéance de nationalité en contexte terroriste – (pluri)appartenance et (sous)citoyenneté en France et au Maghreb - Delphine Perrin (L’Année du Maghreb)
For more than twenty years, terrorist acts have multiplied and spread, affecting many parts of the world, in a post-Cold War context marked by disseminated and deterritorialized violence (Badie, 2016). Most of the attacks affecting the Euro-Mediterranean space, as well as Africa and the Middle East, are claimed to be conducted in the name of a war between civilizations, by jihadist Islamists associated with various groups such as Al Qaeda, and more recently by the self-proclaimed «Islamic State» (also known as Daesh). They are generally committed by European nationals who strike their own country. Even though their profile vary, some are bi-nationals and, in Europe, they often have foreign family origins. The form of terrorism which had affected Europe during the Cold War (the Red Army Fraction in the Federal Republic of Germany, the Red Brigades in Italy, or Direct Action in France) had been handled from an endogenous angle, without bringing the issue of nationality into question despite a similar transnational political situation. In the case of this “new terrorism”, most European states envisage the problem through the central question of national affiliation. In contrast, the Maghreb countries, who are also confronted with the problem of terrorism, do not generally approach it from this angle. Is the variable «Islamist» likely to explain the evolution of the legal framework and the use of forfeiture of nationality, as well as the various approaches between the States around the Mediterranean?